Cerebral venous thrombosis—A primer for the haematologist. Issue 1 (January 2015) - Thorell, Sofia E.; Parry-Jones, Adrian R.; Punter, Martin; Hurford, Robert; Thachil, Jecko
Abstract Cerebral venous thrombosis (CVT) is a condition that can affect all age groups and can often be difficult to diagnose and treat. The difficulties in diagnosis are mainly due to the non-specific presenting features of CVT, which can range from isolated headache and visual or auditory problems, to serious symptoms such as hemiparesis and coma. Therefore, it can present to various specialists including general physicians, obstetricians and neurologists. In recent years, more widespread use of cerebral imaging has led to the diagnosis being made more often. Since thrombosis is the key component, haematologists are consulted in the management of these patients including for identification of a causative factor for CVT. In this regard, the pivotal International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT) has shed more light on its epidemiology and management options. This review aims to provide guidance to haematologists when faced with a patient with CVT, based on the currently available evidence.